2012
DOI: 10.3109/1354750x.2012.709880
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cyanide exposure markers in the biofluids of smokers and non-smokers

Abstract: Cyanide is highly toxic and is present in many foods, combustion products (e.g. cigarette smoke), industrial processes, and has been used as a terrorist weapon. In this study, cyanide and its major metabolites, thiocyanate and 2-amino-2-thiazoline-4-carboxylic acid (ATCA), were analyzed from various human biofluids of smokers (low-level chronic cyanide exposure group) and non-smokers to gain insight into the relationship of these biomarkers to cyanide exposure. The concentrations of each biomarker tested were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…Cotinine is known to be both a metabolite of nicotine and a component of tobacco leaves . While SCN‐ is a metabolite generated in the liver from hydrogen cyanide present in CS, there are no reports regarding the possible presence of SCN‐ in CS or tobacco products. Although many plants are thought to generate SCN‐, we found no detectable SCN‐ in our CSE, as the measured concentrations were below the lower limit of detection of <10 n m .…”
Section: Resultsmentioning
confidence: 99%
“…Cotinine is known to be both a metabolite of nicotine and a component of tobacco leaves . While SCN‐ is a metabolite generated in the liver from hydrogen cyanide present in CS, there are no reports regarding the possible presence of SCN‐ in CS or tobacco products. Although many plants are thought to generate SCN‐, we found no detectable SCN‐ in our CSE, as the measured concentrations were below the lower limit of detection of <10 n m .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Laurberg and colleagues found that smoking, as reflected by nicotine level measured at birth, was associated with an approximately 50 % reduction in BMIC (14) . The reduction in BMIC in smokers is thought to be related to the thiocyanate in cigarettes which acts to inhibit iodine uptake from the maternal circulation into breast milk (14)(15)(16) . Although unexpected, the positive association between BMIC and reported alcohol consumption at study entry is consistent with the results of a national survey of pregnant women in Belgium, which reported that women who were consuming alcohol in the first trimester of pregnancy had a lower risk of iodine deficiency in the first and third IQR, interquartile range.…”
Section: Discussionmentioning
confidence: 99%
“…As summarised in EFSA CONTAM Panel (), a limited number of papers suggest the cyanide metabolites thiocyanate in serum or plasma (ATSDR, ), ATCA in plasma (Lundquist et al., ; Logue, , ; Vinnakota et al., ) and a thiocyanate adduct at Cys 567 formed by reaction of cyanide with the C‐terminal Cys 558 Cys 567 disulfide bond of human serum albumin (Fasco et al., , ) as potential biomarkers for cyanide exposure. Currently, however, there is not sufficient data to determine if useful correlations exist between these potential biomarkers and the internal exposure to cyanide levels.…”
Section: Assessmentmentioning
confidence: 99%